Pengaruh Pendidikan Kesehatan Melalui Whatsapp Reminder terhadap Tingkat Pengetahuan Pencegahan Covid-19 - Putu Gede Surya Swarnata; Ida Erni Sipahutar; NLP Yunianti SC (Jurnal Gema Keperawatan, 2022)
The world was shocked by the outbreak of new pneumonia which started in China, then spread rapidly to more than 190 countries in the world. The impact is almost the entire sector, not only health and economy, but also education. This limitation of the activities affects the pattern of education and all activities that are usually done by Indonesian, then disrupting the movement and dissemination of health information about Covid-19 in the community. Social media can help to increase their knowledge of prevention in dealing with Coronavirus. The purpose of this study was to determine the effect of health education through regular WhatsApp reminders on the level of  knowledge of Covid-19 prevention. This type of research is the One-group pre-post test design. The sampling technique used was proportionate stratified random sampling with a sample size of 81 people. The results showed that the average score of students' preparedness before treatment was 78.23 and after 90.70 with the average difference before and after treatment of 12.47. The results of the study were tested with the Wilcoxon test and the Asymp.Sig value was obtained. = 0.000 (0.05), It can be concluded that there was an effect of health education through periodical-WhatsApp-reminders to the knowledge level of Covid-19 prevention at SMP N 1 Gianyar in 2021. Prevention of Covid-19 through WhatsApp can be developed with interesting, diverse, effective and efficient methods such as video, sound and images.